Performance Analysis and Study of Audio Watermarking Algorithms (International Journal of Engineering and Computer Science, 2014)
Audio Watermark is a signature, embedded within the original signal, which should be inaudible to the human ear and resistant to any attempts to remove it.All audio watermarking schemes contain various parameters in common, in particular robustness,security, transparency, complexity, and capacity. This research work aims to devise a watermarking algorithm that improves the robustness,imperceptibility and speed without affecting the quality of the original host signal..In Echo hiding,the Signal to noise ratio obtained after watermark embedding is 15.3521and the BER is 6.25%.For LSB coding,the SNR obtained for the watermarked signal is 33.8329 and the BER is obtained as 6.25%.For Chirp spread spectrum, the SNR obtained from simulation results is 32.9604 and the error rate obtained is 2.50%.